Thermally efficient fired clay bricks incorporating waste marble sludge: An industrial-scale study. (10th February 2018) - Munir, Muhammad Junaid; Kazmi, Syed Minhaj Saleem; Wu, Yu-Fei; Hanif, Asad; Khan, Muhammad Umer Arif
Abstract: Now-a-days, construction of energy efficient buildings is highly in demand all over the world. The main focus of this study is to utilize waste marble sludge (WMS) in the production of energy efficient burnt clay bricks on industrial scale. For this purpose, WMS was obtained from a local marble industry. Burnt clay bricks were prepared, in an industrial brick kiln under actual field conditions, using various dosages of WMS (i.e., 5%, 10%, 15%, 20% and 25% by weight of clay) and were examined for different physico-mechanical and thermal properties. It was observed that lightweight bricks can be manufactured using WMS, which are helpful in reducing the overall construction costs. Although the reduction in compressive strength was observed with WMS incorporation in clay bricks, 15% replacement level exhibited satisfactory strength requirements. Clay bricks showed increase in apparent porosity and water absorption with increasing WMS content. A porous structure having interconnected and irregular shaped open pores was observed after incorporating WMS in clay bricks, which improved the thermal insulating properties. Brick specimens incorporating up to 15 wt% WMS showed decrease in thermal conductivity by about 16%. Based on this study, 15 wt% WMS is deemed optimum for the manufacturing of burnt clay bricks leading towards sustainable, economical, environment friendly and energy efficient construction. Highlights: Burnt clay bricks were developed utilizing waste marble sludge (WMS). Thermal, physical and mechanical properties of newly developed bricks were studied. WMS can be effectively used to manufacture energy efficient burnt clay bricks.